Stone Fox - Gardiner, John Reynolds; Hargreaves, Greg. (New York : HarperTrophy, 2003)
Little Willie hopes to pay the back taxes on his grandfather's farm with the purse from a dog sled race he enters.
Original copyright: 1980.
Keywords: Sled dog racing -- Juvenile fiction; Dogs -- Juvenile fiction; Grandfathers -- Juvenile fiction; Sled dog racing -- Fiction; Dogs -- Fiction; Grandfathers -- Fiction